Relationship between Education Level, Employment, Socio-Economic Conditions and Stunting Incidents (Case Study in Karanganyar Regency) - Musta'in, Musta'in; Marni, Marni; Sani, Fakhrudin Nasrul; Ramdhani, Ailza (GLOBAL HEALTH SCIENCE GROUP, 2025)
The problem of stunting is a priority for the government to resolve. Stunting is closely related to nutritional problems experienced by toddlers so that the appearance of length and height does not match their age development. Several factors are suspected of influencing the incidence of stunting such as education level, type of work and socio-economic conditions. Central Java Province has several areas that are recorded as having a fairly high incidence of stunting, one of which is in Karanganyar Regency. This study aims to determine the relationship between education level, work, socio-economic conditions and the incidence of stunting in Karanganyar Regency. This study uses primary data obtained by directly interviewing 30 respondents in the research area randomly. The data analysis method used is Pearson correlation. Based on the results of the study, the p-value for the indicator variables of education level and socio-economic conditions is less than the alpha value of 5% so that both have an effect on the incidence of stunting, while the p-value for the type of work is more than the alpha value of 5% so that it does not affect the incidence of stunting.